User orientation through experience: A study of hobbyist knowing in product development - Kotro, Tanja (Human Technology, 2007)
Those who are involved in hobbyist communities and share the values and practices of these communities often also innovate new products. Users are important actors in innovations. Recently, a lot of attention has been paid to users in relation to product development processes and especially user innovations. This article points out that product development team members are often simultaneously users themselves and they can be important translators of "hobbyist knowing" into organizational practices. Hobbyist knowing refers to the practice of making sense of situations through concrete activities and participation in particular social and physical circumstances and practices. This article studies Suunto, the Finnish designer and manufacturer company of sports and precision instruments, and the product development team of wrist computers.